Overcoming the ‘Window Dressing’ Effect: Mitigating the Negative Effects of Inherent Skepticism Towards Corporate Social Responsibility - Connors, Scott (Journal of business ethics, 2017)
As more and more instances of corporate hypocrisy become public, consumers have developed an inherent general skepticism towards firms’ corporate social responsibility (CSR) claims. As CSR skepticism bears heavily on consumers’ attitudes and behavior, this paper draws from Construal Level Theory to identify how it can be pre-emptively abated. We posit that this general skepticism towards CSR leads people to adopt a low-level construal mindset when processing CSR information. Across four studies, we show that matching this low-level mindset with concrete CSR messaging works to effectively mitigate the negative effects of inherent CSR skepticism on consumers’ attitudes, purchase intentions, and word of mouth. The resulting construal-mindset congruency strengthens the favorability of consumer responses through increased positive elaboration and perceptions of CSR message credibility. Furthermore, this congruency effect is shown to persist over time in skeptical domains but to dissipate in less skeptical domains.